Parametric decomposition of the Malmquist index in output-oriented distance function: Productivity in Chinese agriculture - Yu, Bingxin; Liao, Xiyuan; Shen, Hongfang (Scientific Research Publishing, Inc., 2014)
This paper decomposes the Malmquist productivity index into several assembling components: technical change (further break down into technical change magnitude, input bias and output bias), technical efficiency change, scale efficiency change, and output-mix effect. A translog output distance function is chosen to represent the production technology and each component of the Malmquist index is computed using the estimated parameters. This parametric approach allows us to statistically test the hypothesis regarding different components of the Malmquist index and the natural of production technology. The empirical application in Chinese agriculture shows that the average productivity grows at 2 percent per year during 1978-2010. This growth is mostly driven by technical change, which is found to be neutral.